Principal Leadership and School Climate on Vocational High Schools’ School Productivity in Bekasi Regency - Nadeak, Bernadetha (Interdisciplinary Social Studies, 2022)
Graduates of Bekasi's Vocational Schools haven't made much of an impact in business or industry thus far. Vocational High Schools (SMK) with Business and Management Skills in Bekasi Regency have a negative influence because of their low productivity, which is the primary cause of SMK productivity in Indonesia. The purpose of this study is to examine the influence of school climate and leadership on school productivity in the business and management of SMK in Bekasi district. In this study, data was collected through the use of a quantitative technique and an explanatory survey involving a questionnaire. Multivariate regression is used to analyze the data. As a result of this research, we can say: The Business and Management Skills Vocational School in Bekasi Regency's productivity is positively influenced by the leadership of the school's principal, as well as the school's overall climate. The productivity of SMK Business and Management in Bekasi district is greatly influenced by the leadership and school climate at Vocational School in Bekasi Regency. The principle of SMK is advised to maximize the supporting aspects of the school environment, such as the school climate, in order to boost productivity.